The effect of high temperatures on breeding and survival of Japanese quails that are bred under different temperatures - Özbey, O.; Erisir, Z.; Aysöndü, M.H.; Özmen, Ö. (Asian Network for Scientific Information, 2004)
The aim of this study was to determine the effect of higher temperatures on the weight, feed consumption, capacity of benefiting from feed, some carcass features and the survival rates of the Japanese quails placed in different ambiences. Two groups were arranged in this research according to temperature as the control (18-24°C) and trial (35°C) groups, and the quails were placed close together in 120, 90 and 72 cm2 cages for each temperature group. It was observed that the values of the live weight, feed consumption, capacity of benefiting from the feed, and carcass features decreased due to the increase in placement temperature under higher temperatures. In order to minimize the stress that might occur related to the quails under higher temperatures and to ensure the growth performance not to be reduced, it should considered not to place more than 3 quails in an area of 120 cm2. © Asian Network for Scientific Information, 2004.
Keywords: Density stocking; Growing characteristics; Heat stress; Japanese quail